Atomization Characteristics of Gas-Liquid Two Phase Rotation Flow Spray Nozzle - Shi, Ling; Han, Shuyong; Yuan, Wenbo; Xiang, Xiaodong; Yao, Ganying (Asian Journal of Chemistry, 2014)
In order to improve the characteristics of the spray nozzle, a new kind of gas-liquid two-phase rotation flow nozzle is developed. Spray characters and inner velocity distribution for the two-phase rotation flow nozzle are investigated by numerical simulation and experimental measuring, respectively. The simulation results obtained by the computing fluid software, CFX, illustrated that the liquid is changed into a rotary band due to the high gas shear strength. Therefore, the fine water droplets can be easily produced when this two-phase fluid flows to the end of the nozzle. The atomized droplet size is measured by winner 313 spray laser particle size analyzer in the laboratory condition. The experimental data show that the relation of the spray median diameter and the gas-liquid ratio follows a power function. It is helpful to determine the operation parameters for its application in industry.